We will have the following:
![\begin{gathered} x^2-6x+7=k(2x-3)\Rightarrow x^2-6x+7=2kx-3k \\ \\ \Rightarrow x^2-6x-2kx+7+3k=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ns7mn9od1070z47frve18jbhow9eodgcvy.png)
Now, we want to operate like terms and take to "solve for x" using the quadratic expression, that is:
![\Rightarrow x^2+(-6-2k)x+(7+3k)=0\Rightarrow x=(-(-6-2k)\pm√((-6-2k)^2-4(1)(7+3k)))/(2(1))](https://img.qammunity.org/2023/formulas/mathematics/high-school/myrr5ri93wxaapwimfkhnuduy30c1ggcnj.png)
No, in order to determine the possible real values for "k" we have to analyze the value under the root, so:
![\begin{gathered} √((-6-2k)^2-4(1)(7+3k))\Rightarrow(-6-2k)^2-4(1)(7+3k)\ge0 \\ \\ \Rightarrow36+24k+4k^2-28-12k\ge0\Rightarrow8+12k+4k^2\ge0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/klpkyl9qms6h9tm8ubbkb1burzedgwxvxm.png)
Now, we will have to use the quadratic expression again to determine the values for "k" that make the inequality true, that is:
![\begin{gathered} k=(-(12)\pm√((12)^2-4(4)(8)))/(2(4)) \\ \\ \Rightarrow k\leq-2 \\ \\ and \\ \\ \Rightarrow k\ge-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/j30fk9ogj7chf6c9kkp50926ayim0j1tif.png)
So, the values for which the inequality and thus the expression under the root are true are then given by:
![k\leq-2\wedge x\ge-1](https://img.qammunity.org/2023/formulas/mathematics/high-school/cjielmekehz5oaenuj80q6hcutc7ey7keh.png)
In other notation:
![(-\infty,2]\cup[-1,\infty)](https://img.qammunity.org/2023/formulas/mathematics/high-school/zvq1zrbwb2wmjf6f5lfo43fyzi4wx0nfhs.png)